Efficacy of Acceptance and Commitment Therapy on Intimacy, Marital Forgiveness, and Marital Burnout in Women Affected by Extramarital Relationships - Najibzadegan, Arezoo; Bahrainian, Seyed Abdulmajid; Shahabizadeh, Fatemeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to determine the efficacy of acceptance-based therapy in enhancing intimacy and marital forgiveness and reducing marital burnout in women affected by extramarital relationships.Methods: This was a quasi-experimental study with a pretest-posttest and follow-up design, including a control group. The population consisted of all women affected by their husband's extramarital relationships who attended specialized family counseling centers in District 6 of Mashhad. From this group, 30 participants were selected through purposive sampling based on inclusion and exclusion criteria. Data were collected using the Rey et al. (2001) Marital Forgiveness Scale, the Pines (1996) Marital Burnout Scale, and the Thompson and Walker (1983) Marital Intimacy Scale. Participants were then randomly assigned into three experimental groups and one control group, each consisting of 15 individuals. Data analysis was conducted using repeated measures analysis of variance with the Statistical Software Package SPSS-20.Findings: The findings indicated that acceptance and commitment therapy was effective in improving intimacy, marital forgiveness, and reducing marital burnout in women affected by extramarital relationships (P < 0.01). The results were also sustained at the follow-up stage.Conclusion: Therefore, it can be concluded that acceptance and commitment therapy was effective in enhancing intimacy, forgiveness, and reducing marital burnout among women impacted by extramarital relationships, and this therapeutic approach can be utilized to address psychological issues in couples affected by extramarital relationships.